2014
DOI: 10.3109/13816810.2014.886266
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Cone-Rod Dystrophy with High Myopia and Nystagmus Suggests RecessivePROM1Mutations

Abstract: Pediatric cone-rod dystrophies are a genetically heterogenous group of disorders characterized by photophobia, progressive loss of central vision, and subsequent gradual loss of peripheral vision. In general, clinical presentation is not specific for a particular gene mutation; however, there are exceptions, which are important to recognize in order to facilitate molecular diagnosis. In this report, we highlight that pediatric cone-rod dystrophy with high myopia and nystagmus suggests recessive mutations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 9 publications
3
13
1
Order By: Relevance
“…Although previous genetic reports have described numerous PROM1 -associated retinal dystrophy phenotypes, 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 in the current study, we found that the morphological phenotype was associated with cone-rod dystrophy in all cases. The main distinction in phenotypes lies between recessive and dominant forms of the disease.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Although previous genetic reports have described numerous PROM1 -associated retinal dystrophy phenotypes, 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 in the current study, we found that the morphological phenotype was associated with cone-rod dystrophy in all cases. The main distinction in phenotypes lies between recessive and dominant forms of the disease.…”
Section: Discussioncontrasting
confidence: 92%
“…Prominin 1 ( PROM1 ; OMIM 604365 ) is commonly associated with cone-rod dystrophies. 1 However, throughout the literature, variations in PROM1 have been implicated in extremely varied and overlapping phenotypes that have been described as retinitis pigmentosa 2 , 3 , 4 , 5 , 6 , 7 , 8 ; retinitis pigmentosa with macular involvement 9 ; retinal dystrophy 8 ; cone-rod dystrophy 1 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ; bull’s-eye maculopathy 18 ; bull’s-eye maculopathy associated with rod, rod-cone, and macular dystrophy 19 ; Stargardt-like disease 20 , 21 , 22 , 23 ; macular dystrophy 24 ; and maculopathy with rod-cone dystrophy. 25 The age at onset, presenting symptoms, and severity of disease vary with sequence variations.…”
Section: Introductionmentioning
confidence: 99%
“…In the small intestine in mouse, Prom1 marks rare stem cells, as well as transit-amplifying progenitor cells ( 6 ). Moreover, PROM1 is expressed in both rod and cone photoreceptors of the eye ( 18 , 19 ). Prom1 also has been used as a cancer stem cell marker alone or with other markers such as CD44 ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiskan GO (Thermo Fisher) was used to determine the DNA purity and concentration. We developed the IIN capture panel based on Illumina Truseq Custom Amplicon v1.5 kit . The IIN capture panel contains 239 genes ( NYS2, NYS3, NYS4, NYS5, NYS7, ABCA4, ABCB6, PROM1, TYR, PAX6, GPR143, SIX6, DLAT , etc with completed coding regions) with a proven relationship to pathogenesis (genes list available as Appendix ).…”
Section: Methodsmentioning
confidence: 99%